Study Of Animation In Instructional Design For E-Learning Materials: A Framework For Employing Effective Instructional Animations - Heydarbeygi, Arash (2011)
The main themes in this study are (a) areas of consideration (AC), (b) recommended useful principles and theories (RUP), (c) learner side (LS), (d) animation\'s interactivity (AI), (e) subject matter and content (SMC). Finally, from compare and contrasting of analyzed data, this study suggests a framework for instructional designers to design and employ effective animations. It can be used as a quick-guide by designers.